Reconceptualizing interorganizational collaborations as tensile structures: Implications of conveners' proactive tension management. Issue 2 (3rd April 2019) - Woo, DaJung
ABSTRACT: Conveners, as the main organizers of complex inter-organizational collaborations (IOCs), experience tensions as they make decisions based on collaborators' competing interests and ideas. This paper theorizes conveners' tension management as their proactive efforts to shape the IOC processes – as opposed to reactive responses to emergent tensions – and examines how they are related to IOCs' collaborative capacity. A comparative case analysis of two IOCs in regional planning reveals that conveners' organizing practices that actively promoted tensions contributed to creating a more dynamic and tension-resistant collaborative environment, compared to those of conveners who tried to prevent tensions. Using tensile structure as a metaphor, the author theorizes about when and how proactively promoting tensions can enhance collaborative capacity.